2016
DOI: 10.1002/hep.28850
|View full text |Cite
|
Sign up to set email alerts
|

Affinity maturation of a broadly neutralizing human monoclonal antibody that prevents acute hepatitis C virus infection in mice

Abstract: Direct acting antivirals (DAAs) have led to a high cure rate in treated patients with chronic hepatitis C virus (HCV) infection but this still leaves a large number of treatment failures secondary to the emergence of resistance-associated variants (RAVs). To increase the barrier to resistance, a complementary strategy is to employ neutralizing human monoclonal antibodies (HMAbs) to prevent acute infection. However, earlier efforts with the selected antibodies led to RAVs in animal and clinical studies. Therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 21 publications
2
71
0
Order By: Relevance
“…3A). This result may be explained, in part, by the presence in the HCVpp panel of four strains with leucine or isoleucine polymorphisms at the 442 locus in E2, which confer resistance to HC84.26 (16,22). HC84.26 resistance may be slightly exaggerated by this panel, since isoleucine (I) or leucine (L) polymorphisms at position 442 were present in 36% of isolates in this panel of 11 HCVpp, while they are present in only 17% of isolates in the reference panel of 634 genotype 1a and 1b sequences from GenBank.…”
Section: Experimental Inhibitionmentioning
confidence: 99%
See 3 more Smart Citations
“…3A). This result may be explained, in part, by the presence in the HCVpp panel of four strains with leucine or isoleucine polymorphisms at the 442 locus in E2, which confer resistance to HC84.26 (16,22). HC84.26 resistance may be slightly exaggerated by this panel, since isoleucine (I) or leucine (L) polymorphisms at position 442 were present in 36% of isolates in this panel of 11 HCVpp, while they are present in only 17% of isolates in the reference panel of 634 genotype 1a and 1b sequences from GenBank.…”
Section: Experimental Inhibitionmentioning
confidence: 99%
“…We have chosen to focus on this genotype since it is most prevalent worldwide, and no bNAb isolated to date effectively neutralizes all genotype 1 HCV strains (9,22,23,43). While we have selected a panel of genotype 1 HCVpp that is genetically and phenotypically diverse, future studies are needed to confirm and extend these findings using larger panels of genotype 1 HCVpp, as well as HCV from other genotypes.…”
Section: Experimental Inhibitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Polyclonal antibodies from HCV-infected patients were able to protect animal models like humanized mice and chimpanzees from HCV challenge (Bukh et al, 2015; Meuleman et al, 2011; Vanwolleghem et al, 2008). We and others previously reported that neutralizing antibodies targeting the E2 protein could protect from HCV infection in vitro and in vivo (Desombere et al, 2016; Keck et al, 2016; Mesalam et al, 2016). In addition, administration of mAb MBL-HCV1, targeting E2, delayed viral rebound following liver transplantation, while complete protection was reported when combined with the polymerase inhibitor sofosbuvir (Chung et al, 2013; Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 91%